Rapid Application Development (RAD) Method for Developing Clinical Laboratory Information System (case Study: PT. Populer Sarana Medika) - Fardanto Setyatama; Irwan Kurnia Andrianto (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
The use of information technology has transformed laboratory service from conventional way(by using paper/manually) into using computer-based Information System (IS). The output ofcomputer-based IS could also be used for management as service quality improvement. Patient dataalong with their laboratory test result stored electronically in IS become a valuable asset for theclinical laboratory as well as the patient itself. PT. Populer Sarana Medika is trying to utilizeinformation technology as their competitive strategy to improve interoperability with agencies, tointegrate information systems between their departments, and also to improve their overall quality ofservice. This paper mainly discuss about the use of Rapid Application Development (RAD) method inthe development of Clinical Laboratory Information System (CLIS). RAD method could accelerate thedevelopment of IS which is normally done in 180 days (minimum) to only 30-90 days. By using RADmethod, it is expected that the IS would be easier to implement and quicker to develop. The resultshows that CLIS is built within 5 months and the score of ease of use from user is 4.18 out of 5. TheCronbach’s Alpha of the CLIS evaluation questionnaire is 0.748, showing that it is quite reliable(>0.60).